Pengaruh Pengendalian Internal Sistem Kliring Kredit Dan Kesesuaian Kompensasi Terhadap Kecenderungan Kecurangan Akuntansi - Bulan Nettiary Kelara (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2022)
The purpose of this research is to analize the affect of internal control in credit clearing and compensation toward tedency account fraud. There occurs to be two variable in this research which is internal control in credit clearing, compensation, and tedency account fraud. This research uses primary data through questioner distribution as much as 300 questioner with a response rate of 84% (251) which has been distibuted towards bank employees that has already listed as clearing member in Indonesia. Data from the questioner has been treated using SPPS. The result of this research is internal control in credit clearing and compensation has a significant affect toward tedency account fraud.